Дилемма решения Конституционного суда об отмене полномочий правительства по отмене региональных нормативных актов (The Dilemma of the Constitutional Court's Decision Regarding the Abolition of the Government's Authority to Cancel Regional Regulations) - Rohim Nur (SALAM: Jurnal Sosial dan Budaya Syar-i, 2022)
The Constitutional Court (MK) through MK Decision Number 137/PUU-XIII/2015 has canceled the enactment of regulations related to the authority of the Minister of Home Affairs in canceling regional regulations. The judicial review was submitted by the Association of Indonesian Regency Governments (Apkasi). The research method used is a qualitative research method with a literature approach and the Statute Approach. The results of the study stated that the Constitutional Court granted the Petitioner's request as long as the review of Article 251 paragraph (2), paragraph (3), and paragraph (8) and paragraph (4) as long as the phrase '…cancellation of Regency/City Perda and Regent/Mayor Regulation as intended in paragraph (2) is stipulated by a governor's decision as the representative of the Central Government' Law no. 23 of 2014 concerning Regional Government.” This decision of the Constitutional Court was regretted by several parties. Because so far the authority of the Minister of Home Affairs is considered a breakthrough in clearing local regulations that hinder the running of the bureaucracy, for example in matters of investment, taxes, and user fees. As a legal consequence of the Constitutional Court's decision, the Minister of Home Affairs no longer has the authority to cancel regional regulations that violate higher regulations or at the implementation level are deemed problematic or contrary to the public interest. Except through judicial review to the Supreme Court.Keywords: Constitutional Court Decision; Local regulation; Minister of Home Affairs Abstrak:Mahkamah Konstitusi (MK) melalui Putusan MK Nomor 137/PUU-XIII/2015 telah membatalkan berlakunya aturan terkait kewenangan Menteri Dalam Negeri dalam membatalkan peraturan daerah. Uji materi tersebut diajukan oleh Asosiasi Pemerintah Kabupaten Seluruh Indonesia (Apkasi). Metode penelitian yang digunakan adalah metode penelitian kualitatif dengan pendekatan literatur dan Statute Approach. Hasil penelitian menyatakan bahwa Mahkamah Konstitusi mengabulkan permohonan Pemohon sepanjang pengujian Pasal 251 ayat (2), ayat (3), dan ayat (8) serta ayat (4) sepanjang frasa ‘…pembatalan Perda Kabupaten/Kota dan Peraturan Bupati/Wali Kota sebagaimana dimaksud pada ayat (2) ditetapkan dengan keputusan gubernur sebagai wakil Pemerintah Pusat’ Undang-Undang No. 23 Tahun 2014 tentang Pemerintah Daerah.” Putusan Mahkamah Konstitusi  ini banyak disayangkan oleh beberapa pihak. Sebab selama ini wewenang Mendagri dianggap sebagai terobosan dalam membersihkan perda yang menghambat jalannya birokrasi, misalnya dalam urusan investasi, pajak, dan retribusi. Akibat hukum dari Putusan MK ini maka Mendagri tak lagi punya kewenangan untuk membatalkan perda yang menabrak peraturan lebih tinggi atau dalam tataran implementasi dirasa bermasalah atau bertentangan dengan kepentingan umum. Kecuali melalui judicial review ke Mahkamah Agung.Kata Kunci: Putusan MK; Peraturan Daerah; Mendagri